In quest of an authentic identity – an exploratory study of mental health assessment of gender incongruence in urban India - Ketki Ranade; Mohan Raju Shankarappa; Neeraj Kumar; Aryan Somaiya (BMC Psychiatry)
Abstract Last decade in India has seen increasing visibility and dialogue on trans health including gender affirmative interventions. This has been enabled by growing mobilisation and assertion from trans communities and a range of legal and policy changes supporting trans inclusion. In this paper, we focus on mental health assessment of gender dysphoria/ incongruence that is the first and an essential step for a transgender person in the Indian context to be able to access medical and surgical gender affirmative interventions. We discuss findings of a mixed-method, exploratory study conducted with 165 mental health professionals (MHPs) in three cities of India. In this paper we primarily present qualitative data on MHPs’ understanding of gender incongruence, their practice of assessment, rationale for the same and ways in which they end up gatekeeping access to medical and surgical gender affirmative interventions. Concepts such as biological determinism of gender, trans normativity, pathologisation of trans and gender diversity, mental stability and capacity are used to critically discuss findings.